CGAS-STING-TBK1-IRF3/7 induced interferon-β contributes to the clearing of non tuberculous mycobacterial infection in mice. Issue 7 (3rd October 2017) - Ruangkiattikul, Nanthapon; Nerlich, Andreas; Abdissa, Ketema; Lienenklaus, Stefan; Suwandi, Abdulhadi; Janze, Nina; Laarmann, Kristin; Spanier, Julia; Kalinke, Ulrich; Weiss, Siegfried; Goethe, Ralph
Abstract: Type I interferons (IFN-I), such as IFN-α and IFN-β are important messengers in the host response against bacterial infections. Knowledge about the role of IFN-I in infections by nontuberculous mycobacteria (NTM) is limited. Here we show that macrophages infected with pathogens of the Mycobacterium avium complex produced significantly lower amounts of IFN-β than macrophages infected with the opportunistic pathogen M. smegmatis . To dissect the molecular mechanisms of this phenomenon, we focused on the obligate pathogen Mycobacterium avium ssp paratuberculosis (MAP) and the opportunistic M. smegmatis . Viability of both bacteria was required for induction of IFN-β in macrophages. Both bacteria induced IFN-β via the cGAS-STING-TBK1-IRF3/7-pathway of IFN-β activation. Stronger phosphorylation of TBK1 and higher amounts of extracellular bacterial DNA in the macrophage cytosol were found in M. smegmatis infected macrophages than in MAP infected macrophages. After intraperitoneal infection of mice, a strong Ifnb induction by M. smegmatis correlated with clearance of the bacteria. In contrast, MAP only induced weak Ifnb expression which correlated with bacterial persistence and increased number of granulomas in the liver. In mice lacking the type I interferon receptor we observed improved survival of M. smegmatis while survival of MAP was similar to that in wildtype mice. On the other hand, treatment of MAP infected wildtype mice with the IFN-I inducer poly(I:C) or recombinant IFN-β impaired the survival of MAP. This indicates an essential role of IFN-I in clearing infections by MAP and M. smegmatis. The expression level of IFN-I is decisive for transient versus persistent NTM infection.